Association of Interleukin‐10‐1082A/G Polymorphism with Idiopathic Recurrent Miscarriage: A Systematic Review and Meta‐Analysis. (18th December 2015) - Peng, Zheng; Lv, Xiaolan; Sun, Yifan; Dai, Shengming
Abstract : Problem: This systematic review and meta‐analysis aimed to synthesize and assess the correlation between the interleukin‐10 (IL‐10)‐1082A/G polymorphism and idiopathic recurrent miscarriage (IRM) using relevant studies. Method of study: Five electronic databases (Cochrane Library of Systematic Reviews, PubMed, EMBASE, Web of Science, and Google Scholar) were comprehensively searched up to August 2015. Data were extracted independently by two members of our team. Results: The meta‐analysis of 13 eligible studies suggested a recessive effect of the G allele (‐1082A/G polymorphism) for IRM risk. Conclusions: The pooled evidence demonstrated that the GG genotype increased IRM risk.